Penerapan Metode Eksperimen dapat Meningkatkan Aktivitas dan Hasil Belajar IPA Siswa Sekolah Dasar - Suryani Suryani (Universitas Batanghari Jambi, 2018)
This study aims to improve the learning activity and learning outcomes of fifth grade student's SDN. No. 052/XI Ulu Air year 2016/2017 on natural science subjects, especially on the material properties of light through the application of experiment methods. The study was conducted from January to May 2017. The study involved 18 students of fifth grade student's SDN. No. 052/XI Ulu Air year 2016/2017. The study was conducted in two cycles and each cycle consisted of four activities namely planning, implementation, observation, and reflection. Data of learning activity was collected through observation and data of learning outcome was collected through the test. The data that have been collected is analyzed by descriptive analysis and simple statistical test. The results showed that student learning activities improved. The results also showed that the average score of students increased from 52,8 on before action applied to 65,3 in Cycle I and increased to 77,5 in Cycle II. Percentage mastery learning students also experienced an increase from 50,0% in pratindakan to 72,2% in Cycle I and increased to 88,9% in Cycle II. Thus, the experimental method can improve the learning activity and learning outcomes of fifth grade student's SDN. No. 052/XI Ulu Air year 2016/2017 on natural science subjects, especially on the material properties of light.